In silico studies on the interaction of four cytotoxic compounds with angiogenesis target protein HIF-1α and human androgen receptor and their ADMET properties - Jean-Paul Koto-Te-Nyiwa Ngbolua; Jason T. Kilembe; Aristote Matondo; Colette Masengo Ashande; Janvier Mukiza; Célestin Mudogo Nzanzu; Fatiany Pierre Ruphin; Robijaona Baholy; Pius T. Mpiana; Virima Mudogo (Bulletin of the National Research Centre, 2022)
Abstract Background Cancer is a significant public health problem worldwide and constitutes the second leading cause of death after cardiovascular disease. This study was thus designed to identify new natural compounds from Malagasy medicinal plants traditionally used to treat cancer. Methods In silico analyses by molecular docking to model ligand–protein interactions, and by SwissADME and ADMET webservers to establish the pharmacokinetic profile of the four investigated compounds in interaction with the angiogenesis target protein HIF-1α/breast cancer (PDB ID: 3KCX) and human androgen receptor/prostate cancer (PDB ID: 1E3G) were performed. Results The docking results show that the HIF-1α receptor has the best binding energy when it interacts with compound 1 (1′,4-dihydroxy-2,3′-dimethyl-1,2′-binapthyl-5,5′,8,8′-tetraone: − 8.49 kcal/mol) followed by compound 3 [(E)-5,6-dimethyl-2-(2-methyl-3-(prop-1-enyl)phenyl)-2H-chromene: -8.43 kcal/mol], compound 2 (6′-ethoxy-1′3′-dihydroxy-4,6-dimethyl-1,2′-binaphthyl-2,5′,8,8′-tetraone: − 7.80 kcal/mol) and compound 4 (methyl 10-hydroxy-2,4a,6a,9,12b,14a-hexamethyl-11-oxo-1,2,3,4,4a,5,6,6a,11,12b,13,14,14a,14b-tetradecahydropicene-2-carboxylate: − 7.63 kcal/mol). The receptor 1E3G displayed poor binding affinity energy to all tested compounds with energy value above − 11.99 kcal/mol (co-crystal). Based on the H-bonding interaction, ligands 1 and 2 displayed a good pharmacophore profiles to both protein targets 3KCX and 1E3G. Ligand 3 does not interact with the selected receptors via hydrogen bonds. The pharmacokinetic profile of these phyto-compounds revealed that they are orally active and safe. They were isolated and their chemical structures were elucidated previously by our team using chromatographic and spectroscopic techniques (LC/MS/NMR). Conclusions The ligands 1 and 2 can be considered as hits since in addition to their thermodynamic stability with the receptors; they presented a good pharmacokinetic profile and could thus be useful as an alternative therapy in breast and prostate cancer. This study offers a strong potential in developing new, cost-effective, and safe plant-based natural drugs against cancer.